Notes on Indian wolf spiders: II. Genus Hippasa Simon, 1885 (Araneae: Lycosidae, Hippasinae) - Sankaran, Pradeep M.; Caleb, John T.d. (Zootaxa, 2023)
The species of the genus Hippasa described/recorded from India are reviewed based on type and topotype material. Hippasa pantherina Pocock, 1899 stat. rev. is resurrected from synonymy under Hippasa greenalliae (Blackwall, 1867). The following synonymies are proposed: Hippasa charamaensis Gajbe, 2004 syn. nov., Hippasa madhuae Tikader & Malhotra, 1980 syn. nov., Hippasa pisaurina Pocock, 1900 syn. nov. and Hippasa sinai Alderweireldt & Jocqué, 2005 syn. nov., all synonymised with Hippasa deserticola Simon, 1889. Four species, Hippasa fabreae Gajbe & Gajbe, 1999, H. greenalliae, Hippasa hansae Gajbe & Gajbe, 1999 and Hippasa wigglesworthi Gajbe & Gajbe, 1999 are proposed as nomina dubia. The species Hippasa haryanensis Arora & Monga, 1994 is considered as nomen nudum. All the type material examined are illustrated and supplementary descriptions and illustrations are provided for Hippasa agelenoides (Simon, 1884), H. deserticola, Hippasa himalayensis Gravely, 1924, Hippasa loundesi Gravely, 1924, Hippasa lycosina Pocock, 1900, Hippasa madraspatana Gravely, 1924, H. pantherina and Hippasa valiveruensis Patel & Reddy, 1993.